2015
DOI: 10.1177/1077558715579868
|View full text |Cite
|
Sign up to set email alerts
|

How Many Nurse Practitioners Provide Primary Care? It Depends On How You Count Them

Abstract: This study compares different approaches to measuring the number of nurse practitioners (NPs) providing primary care services using data from the 2012 U.S. National Sample Survey of Nurse Practitioners, North Carolina licensing data from 2011, and a 2010 California survey of nurse practitioners and nurse midwives. Estimates of the number and share of NPs providing primary care depend on how one defines primary care. If the definition is based on the field of NP education, the estimated shares in primary care s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 25 publications
(35 reference statements)
0
39
0
Order By: Relevance
“…For NPs in 2014, an estimated 6% of active licenses in the nation were duplicates because NPs were licensed in more than one state (unpublished data from AANP). Whether both licenses were in effect was not assessed but one report identified conundrums in understanding the number and geographical distribution of primary care NPs in two states (Spetz, Fraher, Li, & Bates, ).…”
Section: Discussionmentioning
confidence: 99%
“…For NPs in 2014, an estimated 6% of active licenses in the nation were duplicates because NPs were licensed in more than one state (unpublished data from AANP). Whether both licenses were in effect was not assessed but one report identified conundrums in understanding the number and geographical distribution of primary care NPs in two states (Spetz, Fraher, Li, & Bates, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reviewed studies on NP workforce did not specify NP clinical specialty (i.e., primary care or specialty care). Recent evidence has shown that at least half of NPs did not practice in primary care and instead were in specialty clinical fields (Spetz, Fraher, Li, & Bates, 2015; U.S. Department of Health and Human Services, Health Resources and Services Administration, & National Center for Health Workforce Analysis, 2014). To better understand the role of NPs in health care delivery, it is important that future studies differentiate NP primary care and specialty care practice, thus providing more fine-tuned evidence to inform health care policy.…”
Section: Limitationsmentioning
confidence: 99%
“…These data sources tend to underestimate the number of practicing NPs (Spetz, Fraher, Li, & Bates, 2015) because NPs may not always bill directly (Kaplan et al, 2012), and there are nurses who are licensed or certified as NPs but may not be working as an NP (e.g., they may work in a registered nurse role; HRSA, 2014). …”
Section: Conceptual Basis For the Studymentioning
confidence: 99%